EMPOWERING UNIVERSITY STUDENTS THROUGH SMART LEARNING: A FOCUS ON MOODLE E-LEARNING PLATFORM AND DIGITAL SKILLS - H, Salim; Tauma, H (Advanced Journal of Environmental Sciences (AJES), 2023)
Online education has emerged as a method that combines self-education and distance education by leveraging the Internet to provide educational resources and facilitate interaction among students. The role of teachers in online education goes beyond simply delivering information, as they become educational designers and facilitators, aiming to increase student participation, motivation, and learning. While distance education has a long history, it has recently gained momentum due to advancements in technology. Over time, distance learning has become an alternative to traditional education, offering benefits and flexibility. Various e-learning platforms have been developed to enhance educational experiences, such as the Lima e-learning platform, which focuses on information and communication technology (ICT) topics. Additionally, platforms like COMSON and MODMAT.net have been designed to manage online information and facilitate collaborative research and training. Distributed e-learning platforms have also emerged, offering new e-educational services and innovative testing algorithms. In recent years, blockchain-based e-learning platforms have been developed to improve transparency in assessments and customize curricula. These platforms have the potential to increase trust in online education providers and enhance the credibility of education history and credentials. With the digital age, higher education institutions face the challenge of meeting students’ expectations, which include the integration of information and communication technology, flexibility in learning schedules, and practical applicability of coursework. This necessitates the introduction of new processes and resources while requiring teachers to adapt their teaching methods. The rapid development of technology, including the Internet of Things, artificial intelligence, and big data analysis, has paved the way for smart learning practices. Through the integration of smart devices and technologies, smart learning offers innovative ways to enhance and extend the learning experience. This paper explores the concept of e-learning, discusses the evolution of online education platforms, and highlights the challenges and opportunities presented by smart learning practices